The expression of AURKA is androgen regulated in castration-resistant prostate cancer. Issue 1 (December 2017) - Kivinummi, Kati; Urbanucci, Alfonso; Leinonen, Katri; Tammela, Teuvo; Annala, Matti; Isaacs, William; Bova, G.; Nykter, Matti; Visakorpi, Tapio
Abstract Although second generation endocrine therapies have significantly improved survival, castration-resistant prostate cancer (CRPC) cells are eventually able to escape available hormonal treatments due to reactivation of androgen receptor (AR) signaling. Identification of novel, non-classical and druggable AR-target genes may provide new approaches to treat CRPC. Our previous analyses suggested thatAurora kinase A (AURKA ) is regulated by androgens in prostate cancer cells that express high levels of AR. Here, we provide further evidence that AURKA is significantly overexpressed in AR-positive CRPC samples carrying amplification ofAR gene and/or expressing AR in high levels. We also demonstrate androgen-induced AR binding in the intronic region ofAURKA . The expression ofAURKA is increased upon androgen stimulation in LNCaP-ARhi cells that express high levels of AR. The growth of the cells was also significantly inhibited by an AURKA specific inhibitor, alisertib (MLN8237). Together, these findings suggest that the expression ofAURKA is regulated by androgen in prostate cancer cells that highly express AR, emphasizing its potential as a therapeutic target in patients with CRPC.